2013
DOI: 10.1155/2013/504537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Types of Japanese Honey on Full-Thickness Wound in Mice

Abstract: Although many previous studies reported that honey promotes wound healing, no study has examined the effects of Japanese honey. The aim of this study was to investigate the effects of three types of Japanese honey, Acacia, Buckwheat flour, and Chinese milk vetch honey, on wound healing in comparison with hydrocolloid dressing. Circular full-thickness skin wounds were produced on male mice. Japanese honey or hydrocolloid dressing was applied daily to the mice for 14 days. The ratio of wound area for the hydroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
1
26
0
2
Order By: Relevance
“…However, wound areas Indonesian and Japanese honey did not increase during this phase, but rapidly decreased until the wounds healed by day 14. This result is similar in our previous study (Nakajima, Y., Nakano, Y., Fuwono, 2013). The effect of honey on decreasing wound area because of anti-inflammatory action (Ghaderi, R & Afshar, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, wound areas Indonesian and Japanese honey did not increase during this phase, but rapidly decreased until the wounds healed by day 14. This result is similar in our previous study (Nakajima, Y., Nakano, Y., Fuwono, 2013). The effect of honey on decreasing wound area because of anti-inflammatory action (Ghaderi, R & Afshar, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Japanese already has known honey including Acacia, and Buckwheat honey. Yamada Bee Farm, Okayama, Japan reported Acacia honey is composed of 70.8% glucose and fructose and 18.6% water, and Buckwheat flour honey is composed of 71.2% glucose and fructose and 17.2% water (Nakajima, Y., Nakano, Y., Fuwono, 2013). On the other hand, Indonesia has many of kinds of honey.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…Recently, the potent activity of honey against antibiotic-resistant bacteria has further increased the interest for application of honey. Several honeys have been approved for clinical application [4][5][6]. A review of different antibacterial studies showed that the antibacterial properties of honey depend on the geographical origin of the honey [7] Honey bees has been traditionally recognized as valuable source of energy which contains antibacterial and antifungal proprieties [8].…”
Section: Introductionmentioning
confidence: 99%
“…When used properly, the use of honey is safe and does not involve complications. Japanese honey alone has limited benefit, although it reduces wound size in the inflammatory phase (28) …”
Section: Discussionmentioning
confidence: 99%